1996
DOI: 10.1017/s1357729800014892
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soaking hay fodder for horses on dust and mineral content

Abstract: Four bales of hay were chosen from a stack of hay, barn-stored for 6 months. Each bale was subdivided into four 2-5 kg sections and one section from each bale was subjected to one of four water soaking treatments: 0, 0-5, 3 or 12 h. Post treatment, the samples were shaken for 9 min under a Negretti LS45F personal dust sampler which sampled the surrounding air. The samples were than analysed for levels of respirable particules < 5 jxm in size and for amounts of sodium (Na), potassium (K), phosphorus (P), magnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 15 publications
4
20
0
Order By: Relevance
“…Warr and Petch [5] found a decrease in CP concentration after 12 hours of soaking undescribed hay type, but no effect was observed with 5 minutes-8 hours of soaking. Other studies [4,14,18] have found no effect on CP leaching from a variety of legume, cool season grass, and mixed hays after 20 minutes-16 hours of soaking. In the present study, there was no effect (P < .05) on CP concentration, compared with the control, when flowering orchardgrass and alfalfa-bud hays were soaked (Table 3).…”
Section: The Effect Of Soaking On Cp Concentrationmentioning
confidence: 87%
See 2 more Smart Citations
“…Warr and Petch [5] found a decrease in CP concentration after 12 hours of soaking undescribed hay type, but no effect was observed with 5 minutes-8 hours of soaking. Other studies [4,14,18] have found no effect on CP leaching from a variety of legume, cool season grass, and mixed hays after 20 minutes-16 hours of soaking. In the present study, there was no effect (P < .05) on CP concentration, compared with the control, when flowering orchardgrass and alfalfa-bud hays were soaked (Table 3).…”
Section: The Effect Of Soaking On Cp Concentrationmentioning
confidence: 87%
“…Soaking hay for 30 minutes reduced the respirable particle number by 88%; however, longer soaking periods did not further reduce particle numbers [18].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Horses on the steamed hay and shavings regime were also fed a variety of ways but as previous work has shown [24,25] steaming consistently reduces ARD levels by 99% from hay regardless of contamination level. Moreover, dust-extracted shavings are also uniformly low dust thus less dust will be released into the environment from the forage and bedding so a cleaner environment is ensured if these materials are used.…”
Section: Discussionmentioning
confidence: 99%
“…Slides were stored in a dust-free incubator and left for a minimum of 3 days so that the filter paper could dissolve and counting could be done. Airborne respirable dust was counted at Â40 magnification using a standard laboratory binocular microscope using the procedure detailed by Moore-Colyer [24].…”
Section: Dust Enumeration Proceduresmentioning
confidence: 99%